2021
DOI: 10.3390/cancers13246200
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microbiota in Postmenopausal Breast Cancer Patients and Controls

Abstract: Background: Previous preclinical and clinical research has investigated the role of intestinal microbiota in carcinogenesis. Growing evidence exists that intestinal microbiota can influence breast cancer carcinogenesis. However, the role of intestinal microbiota in breast cancer needs to be further investigated. This study aimed to identify the microbiota differences between postmenopausal breast cancer patients and controls. Patients and methods: This prospective cohort study compared the intestinal microbiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 41 publications
0
19
1
Order By: Relevance
“…In a Dutch study, baseline gut microbiome Shannon index was 5% higher among breast cancer patients in the neoADJ (n = 18) than those in ADJ (n = 63) groups ( p = 0.057). 8 In contrast, baseline alpha diversity measures in our study were lower in the neoADJ than ADJ group ( Table 2 ) but the ADJ group in the previous study was ~5 times larger while the sample size of the neoADJ in the two studies were similar. A second study based on the CANTO cohort collected fecal samples before (n = 76) and after (n = 45) chemotherapy from breast cancer patients and performed analyses combining the neoADJ and ADJ groups 16 .…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…In a Dutch study, baseline gut microbiome Shannon index was 5% higher among breast cancer patients in the neoADJ (n = 18) than those in ADJ (n = 63) groups ( p = 0.057). 8 In contrast, baseline alpha diversity measures in our study were lower in the neoADJ than ADJ group ( Table 2 ) but the ADJ group in the previous study was ~5 times larger while the sample size of the neoADJ in the two studies were similar. A second study based on the CANTO cohort collected fecal samples before (n = 76) and after (n = 45) chemotherapy from breast cancer patients and performed analyses combining the neoADJ and ADJ groups 16 .…”
Section: Discussioncontrasting
confidence: 70%
“…Levels of several taxa (e.g., Ruminococcaceae, Christensellaceae, unclassified Enterobacterales) decreased after completion of chemotherapy while levels of Lactobacillus increased. 8 , 15 However, among breast cancer patients from the CANTO (CANcer Toxicities) cohort with paired samples before and after chemotherapy (35 ADJ, 10 neoADJ), alpha diversity measures increased after chemotherapy compared to before chemotherapy ( p = 0.033). There was a shift of the microbiome composition towards increases in Methanobacteria species and reductions in the abundance of species such as Veillonella that have been associated with worse prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The number of studies on the differences between the gut microbiota of patients and healthy women has been increasing (8)(9)(10)(11)(12), and despite the discrepancies in identified microbial taxa between them, most studies have reported reduced a-diversity in the gut microbiota of women with BC (8,9,12,13). Notably, Zitvogel and colleagues showed that the fecal microbiota composition discriminates groups of patients by tumor size (< or >pT1), grade (G1 and 2 vs G3), axillary node involvement (Nvs N+), and TNM stage (stage I vs stage II/III) (14).…”
Section: Role Of Commensal Bacteria In Bc Growth and Progressionmentioning
confidence: 99%
“…Moreover, the gut microbiota might be the dominant mediator of cancer treatment response (Laborda‐Illanes et al, 2020). In the adjuvant treatment of breast cancer, the use of antibiotics could lead to changes in relative microbiota abundance in patients (Aarnoutse et al, 2021). Thus, the study of gut microbiota in breast cancer was necessary.…”
Section: Introductionmentioning
confidence: 99%